Kajian Atas Putusan Pengadilan Hubungan Industrial Tentang Perselisihan Hak (Studi Kasus PT. Kartika Mitra Sejahtera) (Lex Jurnalica, 2009)
This research utilize research method sentences normatif with secondary data as source of its acquired data through studi documents. Rights dispute is evoked dispute because tidaj be accomplished right for, effect marks sense distinctive performing or interpretation to legislation regulation rule labor agreement, corporate regulation or labor agreement with. Labor agreement that made by and among PT's employ and entrepreneur. Kartika is Partner sejahtera is labor agreement for time one particular. In its performing apparently evoke rights dispute. Employs litigate entrepreneur at industrial's subjective justice attacks. Employ postulates that entrepreneur has done labor agreement breach for time one particular.Â Employ charges to that entrepreneur normatif's rights employ is performed which is pay pay lack because up to work relation happens they accept pay under city minimum wage rule Cilegon and strove for leave rights substitution. To the effect this research is if OHI'S verdict hit labor agreement state for time one particular that changes over to go to Statute appropriate jobholder manpower, what arithmetic about payment lack wages and right for leave which decided by industrial's relationship justice corresponded to labours Law. Keywords: Subjective Justice Verdict Industrial, Rights Dispute, Employer